THE EFFECTS OF DISTRACTION ON SYMPTOMS DURING DRUG PROVOCATION TEST - Cildag, Songul; Senturk, Taskin; Sargin, Gokhan (Medicine and Pharmacy Reports, 2017)
Background. Some patients may have psychosomatic complaints due to their previous experiences during the drug hypersensitivity reaction. Worry about being hurt due to an administered drug is termed nocebo effect, which is the opposite of the placebo effect. In our study, we investigated the effect of distraction on symptoms during drug provocation test. Methods. Our study included 112 patients who underwent DPTs for alternative purposes in our clinic. Previous hypersensitivity reactions of all the patients had objective signs. Patients were divided into two groups for the DPT. Sixty-three patients were kept busy during the test, performing tasks such as filling questionnaires, arranging files in alphabetical and numerical order, and doing archiving (Group 1). Forty-nine patients did not perform any tasks during the test (Group 2). Reactions that occurred during the test were recorded. Results. During the DPT, 5 patients in Group 1 (5/63, 7.9%) and 17 patients in Group 2 (17/49, 34.7%), i.e. a total of 22 patients (22/112, 19.6%), had a reaction. There was a statistically significant difference between Group 1 and Group 2 according to the frequency of the reaction development. Conclusions. Patient psychosomatic complaints during DPTs are proportional to their association with previous allergic reactions. In order to prevent such reactions, it may be beneficial to keep the patients busy with an activity in order to distract them during the test.